2010
DOI: 10.1534/genetics.110.123653
|View full text |Cite
|
Sign up to set email alerts
|

Cdc14-Dependent Dephosphorylation of a Kinetochore Protein Prior to Anaphase in Saccharomyces cerevisiae

Abstract: The budding yeast Cdc14 phosphatase reverses Cdk1 phosphorylation to promote mitotic exit. Although Cdc14 activity is thought to be restricted to anaphase, we found that dephosphorylation of the Dsn1 kinetochore protein in metaphase requires Cdc14. These data suggest that there is a nonnucleolar pool of active Cdc14 prior to anaphase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Dsn1 is the only member of the MIND complex known to contain CDK target sites (22,23), but blocking phosphorylation of these sites does not result in significant mitotic phenotypes (13). To ask whether association of Cdc14 adjacent to the MIND complex could affect phosphorylation of Dsn1, we tagged endogenous Dsn1 with the sequence encoding three HA tags.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dsn1 is the only member of the MIND complex known to contain CDK target sites (22,23), but blocking phosphorylation of these sites does not result in significant mitotic phenotypes (13). To ask whether association of Cdc14 adjacent to the MIND complex could affect phosphorylation of Dsn1, we tagged endogenous Dsn1 with the sequence encoding three HA tags.…”
Section: Resultsmentioning
confidence: 99%
“…However, the importance of these CDK phosphorylation/dephosphorylation events is unclear. For example, Dsn1 is a member of the MIND complex, which is dephosphorylated before the bulk release of Cdc14 (13). However, CDC14 conditional mutants only have a subtle defect in mitosis (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Cdc14 is largely sequestered in the nucleolus until anaphase onset, Dsn1 kinetochore subunit dephosphorylation in metaphase is Cdc14-dependent, suggesting that sufficient levels of Cdc14 may escape nucleolar sequestration and could promote Scc2 dephosphorylation and subsequent cleavage during S phase (43). Further experimentation will be required, however, to determine whether Scc2 is a direct substrate of Cdc14 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Dsn1 is also phosphorylated at three Cdk1 consensus sites (T12, S69, and S264), among which only S264 is conserved within the Saccharomyces lineage (Akiyoshi and Biggins 2010). While studying Dsn1 phosphorylation, we found that the dsn1-S240A, S250A, S264A triple mutant supports growth in the absence of wild-type DSN1 ( Figure 1B).…”
mentioning
confidence: 92%